Decreasing prevalence in cerebral palsy: a multi‐site European population‐based study, 1980 to 2003 - Sellier, Elodie; Platt, Mary Jane; Andersen, Guro L; Krägeloh‐Mann, Ingeborg; De La Cruz, Javier; Cans, Christine; Van Bakel, M; Arnaud, C; Delobel, M; Chalmers, J; McManus, V; Lyons, A; et al. (Developmental medicine and child neurology, 2016)
Aim To monitor the trends in prevalence of cerebral palsy (CP) by birthweight in Europe, 1980 to 2003. Method Data were collated from 20 population‐based registers contributing to the Surveillance of Cerebral Palsy in Europe database. Trend analyses were conducted in four birthweight groups: <1000g (extremely low birthweight [ELBW]); 1000 to 1499g (very low birthweight [VLBW]); 1500 to 2499g (moderately low birthweight [MLBW]); and >2499g (normal birthweight [NBW]). Results The overall prevalence of CP decreased from 1.90 to 1.77 per 1000 live births, p<0.001, with a mean annual fall of 0.7% (95% confidence interval [CI] −0.3% to −1.0%). Prevalence in NBW children showed a non‐significant trend from 1.17 to 0.89 per 1000 live births (p=0.22). Prevalence in MLBW children decreased from 8.5 to 6.2 per 1000 live births (p<0.001), but not linearly. Prevalence in VLBW children also declined from 70.9 to 35.9 per 1000 live births (p<0.001) with a mean annual fall of 3.4% (95% CI −2.4% to −4.3%). Prevalence in ELBW children remained stable, at a mean rate of 42.4 per 1000 live births. Interpretation The decline in prevalence of CP in children of VLBW continues, and confirms that previously reported. For the first time, there is also a significant decline among those of MLBW, resulting in a significant overall decrease in the prevalence of CP. What this paper adds Cerebral palsy (CP) prevalence in children born very low birthweight in 1980 to 2003 further decreased compared to 1980 to 1996. CP prevalence in children born moderately low birthweight has significantly decreased. The result is a significant decrease in the overall CP prevalence. This article is commented on by Smithers‐Sheedy on page 14 of this issue.